Determinants of SMMEs Survival in post-war communities in developing countries: testing the interaction effect of government support - Candiya Bongomin Okello, George; Munene, John C.; Mpeera Ntayi, Joseph; Akol Malinga, Charles (World Journal of Entrepreneurship, Management and Sustainable Development, 2017)
The main purpose of the study is to test the interaction effect of government support in the relationship between business skills, capital adequacy, access to finance, access to market, entrepreneurial education, and Small Medium and Micro-enterprises (SMMEs) survival in post-war communities in northern Uganda. Design/methodology/approach – cross sectional research design was used in the study and quantitative data were collected from 304 SMMEs located in Gulu District using a semi-structured questionnaire. Structural equation modelling (SEM) through use of Analysis of Moment Structures was adopted to establish the interaction effect of government support in the relationship between business skills, capital adequacy, access to finance, access to market, entrepreneurial education and SMMEs survival in post-war communities in northern Uganda. Further, Pearson’s correlation analysis was used to show the association between the variables under study. Findings – the results revealed that there is a significant interaction effect of government support in the relationship between business skills, capital adequacy, access to finance, access to market, entrepreneurial education and SMMEs survival in post-war communities in northern Uganda. Besides, the results indicated that business skills, capital adequacy, access to finance, access to market, entrepreneurial education, and government support have significant and positive impacts on SMMEs survival in post war communities in northern Uganda. Research limitations/implications – the study employed cross-sectional research design, thus, ignoring longitudinal study approach. Besides, the sample was selected from only Gulu District, therefore, leaving out other Districts located in northern Uganda. Practical implications – advocates of recovery programmes and interventions in developing countries should consider government support as a vital factor in promoting business skill, capital adequacy, access to finance, access to market, and entrepreneurial education in order to promote SMMEs survival in post-war communities. In addition, governments in developing countries should offer investment incentives and tax waivers to infant SMMEs in post-war communities like in northern Uganda. Originality/value – the study examined the interaction effect of government support in the relationship between business skills, capital adequacy, access to finance, access to market, entrepreneurial education and SMMEs survival in post-war communities in developing countries. Thus, to the best of our knowledge, this is the first attempt to test the interaction effect of government support in the relationship between business skills, capital adequacy, access to finance, access to market, entrepreneurial education and SMMEs survival in post-war communities in northern Uganda. The use of government support as a moderator in the relationship between business skills, capital adequacy, access to finance, access to market, entrepreneurial education and SMMEs survival is scarce in entrepreneurship literature and theory. This creates uniqueness in this study.
Keywords: Post-war communities; SMMEs survival; Northern Uganda; Access to finance; Government support; Entrepreneurial education